NEW RECORDS AND TAXONOMIC REEXAMINATION OF THE GENUS LABIDOCERA (COPEPODA: CALANOIDA), WITH NOTES ON THEIR SPECIES GROUPS AND DISTRIBUTION IN INDONESIAN WATERS - Mulyadi Mulyadi (Treubia, 1999)
Only few studies on the taxonomy and biogeography of the genus Labidocera from Indonesian waters have been carried out. The present paper deals with relevant information on the description and illustration of eleven species of Labidocera collected from 15 stations in Indonesian waters. Seven out of twelve previously known, i.e., Labidocera acuta Dana, 1849; L. bataviae A. Scott, 1909; L. detruncata Dana, 1849; L. kroyeri (Brady, 1883); L. laevidentata (Brady, 1883); L. minuta Giesbrecht, 1889; L. pavo Giesbrecht, 1889; except L. acutifrons Dana, 1849; L. euchaeta Giesbrecht, 1889; L. madurae A. Scott, 1909; L. nerii Kroyer, 1849; and L. papuensis Fleminger et al., 1982, have been recorded. Two species i.e., L. javaensis Mulyadi, 1997; and L. muranoi Mulyadi, 1997, have been described as new species, and two species i.e., L. bengalensisÂ Krishnaswamy, 1953; and L. sinilobata Shen and Lee, 1963, are new records for the area.